2006
DOI: 10.1007/s10682-005-5877-x
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Growth Patterns in Great tits: Does Increased Selection on Last-hatched Chicks Favour an Asynchronous Hatching Strategy?

Abstract: In birds, competitive abilities of siblings in relation to their sex and the magnitude of hatching delay are still poorly understood. We compared the sex-specific growth of the last-hatched, competitively disadvantaged chicks with that of synchronously hatched chicks in two successive years. Sons exhibited higher growth rates than daughters in a year with delayed onset of breeding, and this sex-related difference was more pronounced among the asynchronously hatched chicks. Females apparently do not selectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Hence, we cannot exclude the possibility that IGF‐1 levels were already in the declining phase in the middle of nestling period. However, we have previously shown that great tit nestling growth rate is highest in the middle of the nesting period (days 6–7 post‐hatch) and decreases substantially towards fledging (Tilgar & Mänd ). This indicates that age‐related changes in IGF‐1 levels from day 8 to day 15 post‐hatch follow the respective changes in somatic growth rate.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, we cannot exclude the possibility that IGF‐1 levels were already in the declining phase in the middle of nestling period. However, we have previously shown that great tit nestling growth rate is highest in the middle of the nesting period (days 6–7 post‐hatch) and decreases substantially towards fledging (Tilgar & Mänd ). This indicates that age‐related changes in IGF‐1 levels from day 8 to day 15 post‐hatch follow the respective changes in somatic growth rate.…”
Section: Discussionmentioning
confidence: 96%
“…Given that increased energy intake sustains higher IGF‐1 secretion to mediate increased growth rate (Ross & Buchanan ; Breier ), we predicted that fledglings in the reduced broods should have higher IGF‐1 levels and therefore more rapid development (increased post‐natal growth rate, better body condition) than those in control and enlarged broods. Also, it has been shown previously that nestling growth rate is highest in the middle of the fledging period (Tilgar & Mänd ); therefore, we expected that plasma IGF‐1 on day 8 post‐hatch would be higher than on day 15, to support more rapid development.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, given that sex differences can exist in the sensitivity of offspring to prenatal (Gorman and Nager 2004) and post-hatching developmental conditions (e.g. Kilner 1998;Oddie 2000;Naguib et al 2006;Tilgar and Mänd 2006), it is surprising that only one study in wild birds has raised the question of whether rearing conditions have sex-specific effects on individuals' future reproductive performance (Gustafsson 1989).…”
Section: Introductionmentioning
confidence: 99%
“…This may be of specific importance to the Egernia system, as being born last may represent a fitness disadvantage, such as reduced survival or growth rate compared with siblings (Massemin et al . 2002; Tilgar & Mand 2006). This would potentially facilitate a parent–offspring conflict with regard to birth order.…”
Section: Discussionmentioning
confidence: 99%